Diversity in Public Library Boards: Perspectives of Board Members - Kumaran, Maha; Templeton, Leanne (Partnership, 2020)
The initial aim of this study was to learn if there was any diversity in ethnicity, sexual orientation, gender, or disability among public library board members. Through participant interviews, this study reports on member perceptions of diversity in the areas of member recruitment, qualifications, training, and length of term. Board members from four public libraries in Alberta and Saskatchewan were interviewed and the results were analyzed through the framework of critical race theory (CRT). Findings suggest that library boards lack diversity, particularly in finding, recruiting, and training members who are truly representative of their community. Cultural sensitivity and cross-cultural training are important for board members to connect with their communities.